2019
DOI: 10.9789/2175-5361.2019.v11i2.297-303
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms in Elderly People / Sintomas Depressivos em Grupos de Terceira Idade

Abstract: Objective:The study's goal has been to identify depressive symptoms in elderly people living in communities or groups in the municipality of Petrolina, Pernambuco State, Brazil, through the Geriatric Depression Scale. Methods: It is a cross-sectional study that was carried out with 185 elderly people. Three structured and semistructured instruments were applied, including the Geriatric Depression Scale. Descriptive statistics and the logit model with Odds Ratio (OR) were used. The Kruskal Wallis and Mann Whitn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
1
0
4
Order By: Relevance
“…Para Oliveira et al (2019) e Maciel (2010) concordam que a família é de grande importância neste momento da vida, pois o processo de envelhecimento torna o idoso mais sensível, emocionalmente e fisicamente, e mais carente em relação ao cuidado e a união. Medeiros (2012) diz ainda que a família é fundamental para o idoso ao lidar com as mudanças provenientes do processo de envelhecimento, pois a família é a fornecedora de cuidados, e é a provedora de um espaço no qual o idoso encontra-se protegido em seus direitos, capaz de manter sua dignidade e identidade.…”
Section: Resultsunclassified
“…Para Oliveira et al (2019) e Maciel (2010) concordam que a família é de grande importância neste momento da vida, pois o processo de envelhecimento torna o idoso mais sensível, emocionalmente e fisicamente, e mais carente em relação ao cuidado e a união. Medeiros (2012) diz ainda que a família é fundamental para o idoso ao lidar com as mudanças provenientes do processo de envelhecimento, pois a família é a fornecedora de cuidados, e é a provedora de um espaço no qual o idoso encontra-se protegido em seus direitos, capaz de manter sua dignidade e identidade.…”
Section: Resultsunclassified
“…10 It was also found that this scale is valid for screening depressive symptoms in the elderly population. 11 The second section also contemplated the defining characteristics and related factors of nursing diagnosis regulation of mood impairment of NANDA-I. 8 The data were analyzed using a quantitative approach, using descriptive statistics for all variables of a univariate nature, including measures of frequency, position and dispersion.…”
Section: Methodsmentioning
confidence: 99%
“…Social factors and related to the health conditions of the elderly person are associated with depressive symptoms, and it is important to develop actions to promote active and healthy aging. alterações biológicas e psicossociais, 1 bem como, diminuição progressiva da reserva funcional, 2 podendo ocasionar problemas de saúde que contribuem para o desenvolvimento da depressão.…”
Section: Conclusion Conclusion Conclusionunclassified
“…A percepção negativa de saúde associada aos sintomas depressivos também é um resultado observado em outros estudos. 1,15,[25][26] Idosos com percepção de saúde ruim ou muito ruim apresentam maior incidência no desenvolvimento de depressão, quando comparados aos idosos que referiam ter boa avaliação de sua saúde. 1 A literatura ainda aponta que a própria percepção ruim ou muito ruim da saúde pode também ser considerada como um sintoma depressivo, 25 além de estar associada a presença de doenças crônicas que são patologias comuns na população idosa.…”
Section: Discussão Discussão Discussão Discussãounclassified
See 1 more Smart Citation